(untitled) - Tremblay, Thom (Indianapolis, IN, 2013)
This full-color Autodesk Official Press guide will help you quickly learn the powerful manufacturing software's core features and functions. Thom Tremblay, an Autodesk Certified Instructor, uses concise, straightforward explanations and real-world, hands-on exercises to help you become productive with Inventor. Full-color screenshots illustrate tutorial steps, and chapters conclude with a related and more open-ended project to further reinforce the chapter's lessons.
Keywords: Đồ họa máy tính,Computer graphics,Three-dimensional display systems